Perbandingan Pengaruh Lama Pengeringan Terhadap Rendemen Minyak Atsiri Kulit Jeruk Manis (Citrus sinensis) dengan Destilasi Uap dan Identifikasi Linalool dengan KLT-Spektrofotodensitometri - suardhika, i made (Jurnal Farmasi Udayana; Vol. 7 No. 2, Tahun 2018, 2018)
This study aims to determine the effect of drying time on the yield of essential oils from orange peel ( Citrus sinensis ) and identify the presence of linalool compounds from essential oils. 300 grams of orange skin samples were dried at 40ºC using an oven with a drying treatment of 0 hours (fresh), 24 hours, and 48 hours. The extraction process is carried out by steam distillation method with attainment of 500 ml of distillate. Essential oils are separated from water using liquidliquid extraction (LLE), so that the essential oils are maximally obtained. The highest yield of essential oil obtained in the sample with a drying treatment for 48 hours is 0.5% (MA3), 24-hour drying obtained a yield of 0.4% (MA2) and the sample without drying provides the smallest yield of 0.2% (MA1). Identification of linalool compounds using TLC-Spectrophotodensitometry was carried out to determine the amount of linalool content seen from the AUC (Area Under Curve). AUC MA3 sample is 39475, MA2 is 35889, and MA1 is 8980. Based on the data obtained can be concluded that the drying duration of the sample affects the yield of essential oils and linalool compounds that obtained.